2023
DOI: 10.3390/molecules28020608
|View full text |Cite
|
Sign up to set email alerts
|

X-H Bond Insertion Promoted by Heterogeneous Dirhodium Metal–Organic Cage with Alkynes as Safe Carbene Precursors

Abstract: A facile and efficient methodology for the generation of the C-X (X = Si, B) bond through a carbene insertion process was demonstrated using a dirhodium metal–organic cage, MOC-Rh-1, as a heterogeneous catalyst. A series of functionalized alkynes were utilized as safe carbene precursors to furnish Si-H and B-H insertion products in moderate to excellent yields. These reactions featured a high atom-economy, a broad substrate scope, and mild reaction conditions. Moreover, the as-prepared MOC-Rh-1 catalyst was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Recently, Chen et al reported a dirhodium metal–organic cage that could also be a good catalyst for Si–H and B–H insertion with enynones as the carbene precursors. 46 Importantly, the catalyst could be recovered easily by simple centrifugation and reused for ten runs without a significant loss in activity, which promotes the utilization rate of the valuable precious metal rhodium.…”
Section: Dirhodium As a Redox-neutral Catalystmentioning
confidence: 99%
“…Recently, Chen et al reported a dirhodium metal–organic cage that could also be a good catalyst for Si–H and B–H insertion with enynones as the carbene precursors. 46 Importantly, the catalyst could be recovered easily by simple centrifugation and reused for ten runs without a significant loss in activity, which promotes the utilization rate of the valuable precious metal rhodium.…”
Section: Dirhodium As a Redox-neutral Catalystmentioning
confidence: 99%
“…Therefore, the development of a new e cient strategy for producing these fused heterocyclic structures is imperative. Building upon our previous research endeavors [31][32][33],…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Tetraphenylethylene (TPE) is a star molecule of AIE materials, widely used due to its simple synthesis, modification, and unusual luminescence. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] A series of eightshaped double macrocycles can be formed by connecting the benzene rings of TPE in pairs (Scheme 1). These structures have received great attention, leading to a series of studies on the AIE mechanism, ion recognition, and multicolor luminescence.…”
Section: Introductionmentioning
confidence: 99%